2018
DOI: 10.5586/asbp.3570
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of individual domains of chloroplast protein AtDeg2 to its chaperone and proteolytic activities

Abstract: The thylakoid protease AtDeg2 is a non-ATP hydrolyzing chloroplast protease/chaperone peripherally connected with stromal side of thylakoid membrane. Its linear structure consists of protease domain and two PDZ domains. To unveil the significance of individual domains, chaperone and proteolytic activities of AtDeg2, its mutated recombinant versions have been developed and their ability to suppress protein aggregation and resolubilization of protein aggregates as well as the ability to degrade substrate protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Besides being a protease, AtDeg2 also has a chaperone activity. Specifically, this protein is able to inhibit the aggregation of denatured lysozyme in vitro [5,6] and can cause in vitro disaggregation of pre-existing aggregates of denatured lysozyme [6]. We have shown that the PDZ2 domain is required both for the chaperone and protease activities of AtDeg2, whereas PDZ1 contributes to the chaperone but not to the protease activity of AtDeg2.…”
Section: Digital Signaturementioning
confidence: 92%
See 4 more Smart Citations
“…Besides being a protease, AtDeg2 also has a chaperone activity. Specifically, this protein is able to inhibit the aggregation of denatured lysozyme in vitro [5,6] and can cause in vitro disaggregation of pre-existing aggregates of denatured lysozyme [6]. We have shown that the PDZ2 domain is required both for the chaperone and protease activities of AtDeg2, whereas PDZ1 contributes to the chaperone but not to the protease activity of AtDeg2.…”
Section: Digital Signaturementioning
confidence: 92%
“…We have shown that the PDZ2 domain is required both for the chaperone and protease activities of AtDeg2, whereas PDZ1 contributes to the chaperone but not to the protease activity of AtDeg2. The protease domain -but not S268 in its catalytic center -was demonstrated to contribute to AtDeg2 chaperone activity [6]. AtDeg1, another non-ATP hydrolyzing chloroplast protease that belongs to the Deg group, was shown to have a chaperone (refoldase) activity as well, which probably requires protease domain because substitution of the proteolytically active serine residue (S280) by the proteolytically inactive alanine residue (A) considerably reduced the refoldase activity of AtDeg1.…”
Section: Digital Signaturementioning
confidence: 99%
See 3 more Smart Citations